Parents' involvement in the education of their children in primary schools in the Ga East district of greater Accra region of Ghana: Parents' involvement in the education of their children in primary schools in the Ga East district of greater Accra region of Ghana (Journal of Educational Management, 2012)
The concern for the home to play a more active and complementary role in promoting quality education of children is on the increase in many societies throughout the world, including Ghana. The purpose of the study was to examine the level of parents' involvement in the education of their children in primary schools in the Ga East District of Greater Accra Region. The research design was phenomenological. Fifty respondents made up of 10 headteachers, 20 teachers and 20 parents were involved in the study. Purposive sampling was used to select the heads and teachers of the schools while simple random sampling was used to select the parents. Unstructured interview was the only instrument used to elicit information from the respondents. The study found among others that most of the parents in the district were highly involved in the education of their wards. It was suggested that parents, especially working mothers should be encouraged to play a more meaningful role in the education of their children by providing them with a quiet place to study, helping them with homework, being firm about bedtime, monitoring their academic and social behaviours and providing them with their school needs, among others.